Endogenously generated arachidonate‐derived ligands for TRPV1 induce cardiac protection in sepsis. Issue 7 (20th February 2018) - Chen, Jianmin; Hamers, Alexander J. P.; Finsterbusch, Michaela; Massimo, Gianmichele; Zafar, Maleeha; Corder, Roger; Colas, Romain A.; Dalli, Jesmond; Thiemermann, Christoph; Ahluwalia, Amrita
Abstract : The severity of cardiac dysfunction predicts mortality in sepsis. Activation of transient receptor potential vanilloid receptor type (TRPV)‐1, a predominantly neuronal nonselective cation channel, has been shown to improve outcome in sepsis and endotoxemia. However, the role of TRPV1 and the identity of its endogenous ligands in the cardiac dysfunction caused by sepsis and endotoxemia are unknown. Using TRPV1 −/− and TRPV1+ / + mice, we showed that endogenous activation of cardiac TRPV1 during sepsis is key to limiting the ensuing cardiac dysfunction. Use of liquid chromatography‐tandem mass spectrometry lipid analysis and selective inhibitors of arachidonic metabolism suggest that the arachidonate‐derived TRPV1 activator, 20‐hydroxyeicosateraenoic acid (20‐HETE), underlies a substantial component of TRPV1‐mediated cardioprotection in sepsis. Moreover, using selective antagonists for neuropeptide receptors, we show that this effect of TRPV1 relates to the activity of neuronally released cardiac calcitonin gene‐related peptide (CGRP) and that, accordingly, administration of CGRP can rescue cardiac dysfunction in severe endotoxemia. In sum activation of TRPV1 by 20‐HETE leads to the release of CGRP, which protects the heart against the cardiac dysfunction in endotoxemia and identifies both TRPV1 and CGRP receptors as potential therapeutic targets in endotoxemia.—Chen, J., Hamers, A. J. P., Finsterbusch, M., Massimo, G., Zafar, M., Corder, R., Colas, R. A., Dalli, J., Thiemermann, C., Ahluwalia, A. Endogenously generated arachidonate‐derived ligands for TRPV1 induce cardiac protection in sepsis. FASEB J. 32, 3816–3831 (2018). www.fasebj.org